A Comprehensive Systematic Review of Efficacy of Exercise in Managing COPD - Aditya Kafi Amrullah; Syarifudin; Reza Gusni Saputra (The International Journal of Medical Science and Health Research, 2025)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of global morbidity and mortality, characterized by persistent respiratory symptoms and airflow limitation. Beyond pharmacological management, non-pharmacological interventions, particularly structured exercise training, are cornerstones of comprehensive care. This systematic review synthesizes evidence on the efficacy of various exercise interventions across the spectrum of COPD severity. Methods: A systematic literature screening was conducted on 80 sources, including randomized controlled trials (RCTs), systematic reviews, and meta-analyses. Studies were included if they involved adults (≥18 years) with confirmed COPD, examined structured exercise interventions (e.g., pulmonary rehabilitation, aerobic, resistance, traditional exercises), and reported on COPD management outcomes (exercise capacity, quality of life, dyspnea, exacerbations). Data were extracted on intervention characteristics, population demographics, primary and secondary outcomes, effect sustainability, study quality, and proposed mechanisms. Results: Exercise training consistently produced clinically significant improvements. Functional exercise capacity (6-minute walk distance) improved by a mean difference (MD) of 43.93 meters (exceeding the MCID of 30m) (McCarthy et al., 2015). Health-related quality of life showed meaningful gains in Chronic Respiratory Disease Questionnaire (CRQ) domains (MD 0.56-0.79) and St. George's Respiratory Questionnaire (SGRQ) total score (MD -6.89) (McCarthy et al., 2015). Dyspnea was significantly reduced (MRC score MD -0.64), and muscle strength increased (SMD 0.6 for resistance training) (Troosters et al., 2010; de Lima et al., 2020). Benefits were observed across settings (hospital, community, home), with home-based programs proving non-inferior to hospital-based for dyspnea outcomes (Wuytack et al., 2018). Supervised maintenance exercise reduced respiratory hospital admissions (RR 0.62) (Jenkins et al., 2018). Effects on lung function were generally modest, though traditional Chinese exercises showed significant improvements in FEV1 (Luo et al., 2016). Benefits tended to attenuate after 12 months without structured maintenance. Discussion: Exercise efficacy is mediated by multifaceted physiological (improved muscle oxidative capacity, reduced dynamic hyperinflation) and psychological (enhanced self-efficacy) mechanisms. Heterogeneity in outcomes is influenced by disease severity, intervention characteristics (duration, intensity, modality), and program setting. Key challenges include sustaining long-term benefits and ensuring adherence. The integration of behavioral strategies and accessible formats (home-based, telerehabilitation) is crucial for lasting impact. Conclusion: Structured exercise is a highly effective, safe, and essential component of COPD management, delivering clinically meaningful improvements in exercise capacity, symptoms, quality of life, and healthcare utilization across all disease stages. Future efforts should focus on personalizing interventions, developing effective long-term maintenance strategies, and improving equitable access through innovative delivery models.